A conformable high temperature nitride coating for Ti alloys. (1st May 2020) - Gao, Zhaohe; Zhang, Zhenbo; Zhang, Xun; Kulczyk-Malecka, Justyna; Liu, Han; Kelly, Peter; Withers, Philip J.; Xiao, Ping
Abstract: There are many applications including aeroengine design where one would like to operate Ti or its alloys at higher temperatures, but the threat of oxidation or fire remains a longstanding challenge. Here, we have designed a bilayer nitride coating for Ti and its alloys produced by magnetron sputter deposition of a SiAlN coating (1.2 μm thick) along with a Mo interlayer. We have taken advantage of interdiffusion and inter-reaction at the interface during cyclic oxidation at 800 °C to form a layered nitride coating system comprising: a SiAlN top layer, a TiN0.26 and Ti5 Si3 mixed phase interlayer, and a Ti-Mo solid solution. The novel TiN0.26 interlayer exhibits adaptive conformability via mechanical twinning, thereby accommodating the thermal mismatch strain between the coating and substrate. This, along with high adhesion, confers excellent thermal cycling life with no cracking, spallation and oxidation of the coating, evident after hundreds of hours of cyclic oxidation (>40 cycles) in air at 800 °C. This work provides a design pathway for a new family of coatings displaying excellent adhesion, adaptive conformability and superior environmental protection for Ti alloys at high temperature. Graphical abstract: Image, graphical abstract